A novel facile transformation to 1, 2-bis(3-nitro-1-(1H-tetrazol-5-yl)-1H-1, 2, 4-triazol-5-yl)hydrazine salts. (9th August 2018) - Zhao, Baojing; Li, Xingye; Wang, Piaopiao; Ding, Yongzhi; Zhou, Zhiming
Abstract : A facile and unique conversion from NN group to HN–NH group was discovered, by which 1, 2-bis(3-nitro-1-(1 H -tetrazol-5-yl)-1 H -1, 2, 4-triazol-5-yl)hydrazine and its energetic salts have been readily prepared as high-energy-density materials. Abstract : A novel high-nitrogen compound, 1, 2-bis(3-nitro-1-(1 H -tetrazol-5-yl)-1 H -1, 2, 4-triazol-5-yl)diazene, was designed and synthesized. The corresponding hydrazine energetic salts were prepared through spontaneous reductive conversion by structurally varied amino salts. All energetic salts showed good thermal stabilities with decomposition temperatures ranging from 212 to 259 °C, and high positive heats of formation in the range of 411.1 to 1554.7 kJ mol −1 . Furthermore, hydroxyammonium salt featured a promising integrated energetic performance ( v D = 9038 m s −1, IS = 8 J, and FS = 360 N), which is superior to that of RDX ( v D = 8890 m s −1, IS = 7.4 J, FS = 120 N), showing promising properties for new high-nitrogen high-energy-density materials.